Dissipation and risk assessment of select insecticides used for pest management in cabbage and cauliflower - Anju Padmanabhan (Department of Agricultural Entomology, College of Agriculture, 2018)
Studies on “Dissipation and risk assessment of select insecticides used for pest management in cabbage and cauliflower” was conducted in College of Agriculture, Vellayani, Cardamom Research Station, Pampadumpara and farmers field at Kalliyoor during 2015-2018. The present research work was under taken to study the dissipation of select insecticides viz., chlorantraniliprole 18.5 % SC, flubendiamide 39.35 % SC, indoxacarb14.5 % SC, emamectin benzoate 5 % SG, fipronil 5 % SC, quinalphos 25 % EC, cypermethrin 10% EC, acetamiprid 20% SP, thiamethoxam 25 % WG and dimethoate 30 % EC in cabbage and cauliflower, to assess their potential risks to human health, to determine their effect on soil microbial activity, to estimate the residues in cooked samples and to evaluate the efficacy of “Veggie Wash” to eliminate residues. Survey conducted among 25 each of farmers cultivating cabbage and cauliflower in plain (Thiruvananthapuram) and hill (Idukki) representing two agro climatic conditions revealed that pest infestation was more in hills when compared with plains. Accordingly, pesticide usage was higher in Idukki (84 % each) than in Thiruvananthapuram district (12 and 8 %) in cabbage and cauliflower respectively. Dissipation studies of insecticides having label claim for cabbage and cauliflower under CIB & RC in two agroclimatic regions of Kerala viz., Thiruvananthapuram and Idukki showed that the degradation of insecticides varied with crop and chemistry of the insecticides. Insecticides persisted more in cabbage under plain were flubendiamide (20 days) followed by acetamiprid and quinalphos (10 days each), while in hills, higher persistence was observed in flubendiamide, cypermethrin and quinalphos (10 days each). The lowest persistence was observed in fipronil (3 days) in cabbage under plains and acetamiprid (3 days) in hills. In cauliflower higher persistence was observed for flubendiamide, chlorantraniliprole and dimethoate in plains and flubendiamide, quinalphos (20 days each) and cypermethrin (15 days) treated plots in hills. The lowest persistence was observed for emamectin benzoate (3 days) in cauliflower under plains and hills. Risk assessment study was carried out in cabbage and cauliflower using selected insecticides under plains and hills by comparing the values of Theortical Maximum Residue Concentration (TMRC) and Maximum Permissible Intake (MPI). The result revealed that consumption of dimethoate and fipronil treated cabbage and cauliflower were found to be risky to the end users. However, all other insecticides are safe even on the same day of insecticide application. Effect of insecticides on soil microbial activity was studied in cabbage and cauliflower through the activity of urease, phosphatase and dehydrogenase enzymes. Lower reduction in urease activity was observed in flubendiamide, dimethoate and thiamethoxam treated plot and higher reduction was recorded in fipronil and quinalphos treated plots over control both in cabbage and cauliflower. However, lower reduction in phosphatase activity was recorded in flubendiamide, thiamethoxam and cypermethrin and higher reduction was observed in indoxacarb and fipronil treated plots over control. Lower reduction in dehydrogenase activity was recorded in cypermethrin, acetamiprid and thiamethoxam treated plots and higher reduction was recorded in indoxacarb and fipronil treated plots over contol in both cabbage and cauliflower. Study on extent of removal of insecticides through cooking from cabbage and cauliflower was conducted with insecticides which had more persistence revealed that 15 min cooking removed more residues and the highest removal was observed for quinalphos (54.79 %) in cabbage under plains and cypermethrin (66.47 %) in hills. However, in cauliflower the highest per cent removal was observed for chlorantraniliprole (44.78) in plains and cypermethrin (52.32 %) in hills. “Veggie wash” technology was evaluated in the cabbage and cauliflower after application of insecticides at recommended doses revealed that dipping of cabbage and cauliflower in one per cent “Veggie Wash” solution for 10 min. followed by water wash removed 12-40 per cent of treated insecticides while water wash alone removed 9 -35 per cent. The present study revealed that the dissipation pattern of insecticides varied with crop, agro climatic areas, and chemistry of the molecules. Risk assessment study shown that insecticides viz., fipronil and dimethoate posed risk on human health even at recommended dose. Studies on effect of insecticides on soil enzyme revealed that except fipronil and indoxacarb, all other insecticides under present study have less impact on soil enzymes. Decontamination studies showed that cooking at 15 min. removed 50-60 per cent of insecticides and “Veggie Wash” removed 12-40 per cent of treated insecticides. Present study urged the need to evaluate the new insecticides carefully, by considering safety to environment and human health. The risk assessment studies of all insecticides should be done before going for field level recommendations.